Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1093/cid/ciw213
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Drug Resistance Among Children and Youth in the United States With Perinatal HIV

Abstract: Among 234 US youths with perinatal human immunodeficiency virus, 75% had antiretroviral resistance, substantially higher than that of the reference laboratory overall (36%-44%). Resistance to newer antiretrovirals and to all antiretrovirals in a class was uncommon. The only factor independently associated with future resistance was a higher peak viral load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 12 publications
0
21
1
Order By: Relevance
“…Older PHIVY had greater early exposure to mono- or dual-regimens compared to younger PHIVY; the lack of viral suppression among those PHIVY prescribed cART is more likely related to poor medication adherence or acceptance, as resistance to newer ARVs, such as integrase inhibitors, is uncommon. 35 Older youth also spent more time with CD4 counts <200/μL. Data from PHIVY aged 6–17 suggest that having CD4 counts <200/μL is associated with lower quality of life, psychiatric symptoms, and poor cognitive, academic, and social functioning, and data from adults suggest high risks of OIs and death.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Older PHIVY had greater early exposure to mono- or dual-regimens compared to younger PHIVY; the lack of viral suppression among those PHIVY prescribed cART is more likely related to poor medication adherence or acceptance, as resistance to newer ARVs, such as integrase inhibitors, is uncommon. 35 Older youth also spent more time with CD4 counts <200/μL. Data from PHIVY aged 6–17 suggest that having CD4 counts <200/μL is associated with lower quality of life, psychiatric symptoms, and poor cognitive, academic, and social functioning, and data from adults suggest high risks of OIs and death.…”
Section: Discussionmentioning
confidence: 98%
“…Complications potentially related to long-term antiretroviral therapy, including anemia, pancreatitis, hepatitis, peripheral neuropathy, and metabolic and bone abnormalities, were documented infrequently, likely reflecting use of less toxic ARVs over time. 35,51 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Among PHIV youth in both high-and low-and-middleincome countries, mental health problems are common, and some PHIV youth engage in high-risk behaviors, [4][5][6][7] including substance use, sexual risk-taking, and inconsistent condom use. [8][9][10] ART adherence rates among PHIV adolescents are also lower than among adults and younger children living with HIV, 11 increasing risk to individual health and of HIV transmission to others.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies from the USA and sub-Saharan Africa have found that PHIV+ youth, similar to same age peers, are engaging in substance use and sexual behaviors, and use condoms inconsistently (Bauermeister, Elkington, Robbins, Kang, & Mellins, 2012 ; Birungi, Mugisha, Obare, & Nyombi, 2009 ; Mellins et al., 2011 ; Tassiopoulos et al., 2013 ). Furthermore, PHIV+ adolescents and young adults have lower levels of medication adherence and higher levels of drug resistance relative to younger children and adults (Van Dyke et al., 2016 ), increasing risk of adverse medical outcomes and transmission of HIV to others.…”
mentioning
confidence: 99%